International Cooperation on Climate Protection is Promoted by IFIs - G. Ahamer (Финансы: теория и практика)
The author explores various aspects of cooperation of International Financial Institutions (IFIs) between themselves (blending), as well as with state and commercial structures of different countries in the field of solving international problems related to climate change on the planet. The aim of the article is to describe the role of IFIs, forms of cooperation and the financial instruments used for funding activities for sustainable economic development and solving climate problems in the world and in individual states. The author applies general scientific cognition methods, such as analysis, synthesis and systemic approach. The study generalizes the experience of IFIs in addressing the issues based on international statistics in areas such as sustainable economic development and global climate change. The paper provides the statistical analysis of individual countries, in particular, in the Central Asian region. The author makes a conclusion about the importance of the dialectical interconnection between the methods of collective and individual learning in solving global problems, as well as the development of universal procedures, instruments and criteria for assessing the achievement of goals. The formulated proposals may be of further use to regulators, relevant ministries and departments, as well as companies in cooperation with IFIs in the implementation of infrastructure and climate protection projects.